A new method for computing continuous functions with fuzzy variable - Muhammad Zaini, Ahmad; Hasan, M.K.; De Baets, B. (Asian Network for Scientific Information (ANSInet), 2011)
Link to publisher's homepage at http://www.ansinet.com/